1988
DOI: 10.1523/jneurosci.08-09-03451.1988
|View full text |Cite
|
Sign up to set email alerts
|

The location of cues promoting selective reinnervation of axolotl muscles

Abstract: The selective reinnervation of muscles suggests that muscles have intrinsic recognition cues that promote selective synaptogenesis. For example, the anterior and posterior heads of the axolotl iliotibialis (ILT) muscle are preferentially reinnervated by their original motoneurons even after surgically exchanging them. The nature and location of cues that promote such selectivity are unknown, although previous work suggests that the muscle fibers themselves might harbor the relevant molecules. To address this q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The specificity between a single neuron and its endplate is established during development with the competitive elimination of redundant innervation [17]. Following denervation in the adult, motoneurons revert to a more embryonic or dedifferentiated state, but retain some specificity for their original muscle target [18][19][20]. Denervation induces formation of extrajunctional (de novo) receptors on each muscle fiber [21].…”
Section: Discussionmentioning
confidence: 99%
“…The specificity between a single neuron and its endplate is established during development with the competitive elimination of redundant innervation [17]. Following denervation in the adult, motoneurons revert to a more embryonic or dedifferentiated state, but retain some specificity for their original muscle target [18][19][20]. Denervation induces formation of extrajunctional (de novo) receptors on each muscle fiber [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments have demonstrated that selective reinnervation of muscles can occur (Wigston andSanes, 1982,1985;Laskowski and Sanes, 1987;Wigston and Kennedy, 1987). It has been suggested that muscles possess intrinsic recognition cues that promote selective reinnervation, even when muscles are transplanted to novel locations (Wigston, 1986) and that some of this selectivity can be abolished by destroying a muscle's fibers (Wigston and Sanes, 1985;Wigston and Donahue, 1988). It is possible that these postulated recognition cues are generally compartment-specific and that this specificity underlies the selective innervation of neuromuscular compartments that we have observed at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Selective reinnervation has been reported to occur after transection of motor axons in neonatal rats, 2,14 larval anurans, 10 and adult urodeles. 29 Hardman and Brown 14 demonstrated that reinnervation of intercostal muscles of neonatal rats was topographically correct, whereas reinnervation in adult rats appeared to be random. Further, Gillespie et al 12 demonstrated nonselective innervation of rat lateral gastrocnemius and soleus muscles when the common nerve branch to these muscles was cut and sutured to the lateral gastrocnemius muscle.…”
mentioning
confidence: 99%